Evaluation of exchanged clones in high rainfall area of Southern Thailand - Nathaworn, C.D.; Rodesuchit, A., Tueaksuban, S., Yuttimit, S., Ningrawee, W., Injaeng, P., Nirapathpongporn, K. and Piyatrakul, P. (Proceedings of the IRRDB International Rubber Conference 2023, 20-21 February 2023, IRRDB, Kuala Lumpur, Malaysia, pp. 12-16.)
Nineteen exchanged clones and three recommended clones (PB 260, RRIM 600 and RRIT 25) were evaluated over the first nine years of tapping under 1/2s- d/2 tapping system in high annual rainfall at Ranong province in Southern Thailand. The observation traits were yield (g/t/t, kg/ha/year), girth increment, tapping panel dryness (TPD), wind damage and resistance to leaf diseases. During the immature phase, when the trees were seven years of age, the best-growing clone was IRCA 101 (girth 59.68 cm), whereas the worst clone was RRIM 600 (girth 48.66 cm). After the commencement of tapping, the best-growing clones were PB 314 followed by IRCA 825 and IRCA 101 with girths 80.44, 79.87 and 77.05 cm, respectively. Dry yield collected for nine years of tapping showed that IRCA 101 was the best clone followed by PB 260, IRCA 18, RRIC 130, IRCA 317, RRIM 901, IRCA 122, IRCA 41, PB 314, IRCA 631, IRCA 825 and IRCA 871 with yield 2027, 2008, 1927, 1908, 1901, 1872, 1710, 1708, 1697, 1683, 1678 and 1664 kg/ha/year, respectively. Clones resistant to powdery mildew were RRIM 901, RRIC 130, RRIC 131, RRIC 133, IRCA 109, IRCA 122, IRCA 144, IRCA 317, IRCA 523, IRCA 825 and IRCA 871. Except RRIM 600 and RRIC 133, all other clones were moderately resistant to Phytophthora leaf fall disease. Circular leaf spot disease, the new blight that plagues the rubber industry was first observed in this area in August 2021.
Keywords: High rainfall; Rubber yield; Girth; Leaf disease; Clone exchange